The Impact of COVID-19 Pandemic on Romanian Modern Grocery Retailers - Andreea Elena Strătilă (Irimia); Mihai Mehedințu (Journal of Emerging Trends in Marketing and Management, 2020)
The purpose of this paper is to see how Romanian modern grocery retailers have been impacted during COVID-19 outbreak and how should they respond to the new customer behavior changes. The literature review reveals previous findings regarding consumer behavior changes during SARS and MERS epidemic, poor recent findings about COVID-19 outbreak impact, the premises and disruptions that could predict a possible new crisis in the next future of retailing and the strategies adopted by grocery retailers during past crisis. The paper also presents a case study research made on 4 international retail chains that are operating in Romanian modern grocery retailing sector, based on their Facebook communication during Covid-19 outbreak. Finally, are presented the conclusions and recommendations. The research finds the new customer expectations during a stressful and anxious period caused by going out restrictions and reveals the main attributes that could influence people engagement on the selected retailers Facebook pages and where to shop decision. This study is an important tool for practitioners in order to be proactive and gain competitive advantage by enhancing the communication on Facebook, in a specific period that may precede a crisis but also because it is not known when it will end.